Economic regulation: an approach totheoretical and conceptual framework - Romero-Alvarado, Luz Marina (Universidad Pedagógica y Tecnológica de Colombia, 2015)
The article presents the main postulates and approaches of the regulation: the public interest and the private interest. The first, that followed the foundations of Keynesian welfare theory, had its origin in the state intervention in the economy towards the thirties of the 20th century, through the regulation to correct market failures generated by neoclassica l assumptions. The second arises towards the seventies of the same century, faced strong criticism and controversy to the traditional regulatory model, due to the failures of the government to practice regulation in addition to the market failures.